2015
DOI: 10.1111/iep.12132
|View full text |Cite
|
Sign up to set email alerts
|

Expression and significance of cortactin and HDAC6 in human prostatic foamy gland carcinoma

Abstract: Cortactin, the cytoplasmic substrate of HDAC6, is known to play an actin cytoskeletal regulatory role which is implicated in the motility of cancer cells, and thus in cancer progression. Its activity is found to be regulated by HDAC6. However, the significance of cortactin and HDAC6 remains unclear in uncommon histologic variant human prostatic foamy gland carcinoma (PfCa). In this study, we aimed to identify the expression and potential role of cortactin and HDAC6 in PfCa. Therefore, 16 PfCa specimens contain… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 23 publications
1
8
0
Order By: Relevance
“…The recorded electrochemical signals presented in Table 2 demonstrate the upregulation of miR-106a in the serum samples of GC patients, which was anticipated according to the literature [23]. As references, the expression level of the serum miR-106a was simultaneously quantified by qRT-PCR after an extra RNA extraction step.…”
Section: Resultssupporting
confidence: 58%
See 2 more Smart Citations
“…The recorded electrochemical signals presented in Table 2 demonstrate the upregulation of miR-106a in the serum samples of GC patients, which was anticipated according to the literature [23]. As references, the expression level of the serum miR-106a was simultaneously quantified by qRT-PCR after an extra RNA extraction step.…”
Section: Resultssupporting
confidence: 58%
“…In spite of recent advances in diagnostic techniques and pre-operative management, the prognosis of patients with advanced disease is still poor, even in the developed countries [2]. The most commonly used tumor markers such as carcinoembryonic antigen (CEA) and cancer antigen 19-9 (CA19-9) have insufficient sensitivity and specificity, thus limiting their application in early diagnosis of GC [3]. Therefore, the establishment of novel strong specific biomarkers with sufficient sensitivity is an ideal strategy for improving the early detection of GC and the cure rates for patients.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A large number of researches had demonstrated that cortactin was correlated with the prognosis of various tumors, including OSCC [25][26][27]. In the study of Li et al, they reported that the negative expression of cortactin was an independent prognostic factor and had a survival advantage in epithelial ovarian cancer [28].…”
Section: Discussionmentioning
confidence: 99%
“…Histone deacetylase 6 (HDAC6) belongs to the HDACs family and is prominently involved in carcinogenesis and cancer progression [102,103]. Numerous studies have found that high expression of HDAC6 exists in several human cancers and is associated with a significantly poor prognosis in diseases such as breast cancer [104] and PrCa [105]. HDAC6 contains two functional catalytic domains and deacetylates many nonhistone oncogenic proteins [103].…”
Section: Colorectal Cancer (Crc)mentioning
confidence: 99%